Pengaruh Model Pembelajaran Kooperatif Tipe Teams Games Tournament terhadap Peningkatan Hasil Belajar Kognitif Siswa pada Materi Zat Aditif - Afifatus Shofa; Oktaffi Arinna Manasikana; Rofiatul Hosna (CAHAYA: Journal of Research on Science Education, 2026)
This research is based on the low cognitive learning outcomes and the lack of active participation of students in the science subject, particularly in the contextual material of additives. This study aims to examine the implementation of the Teams Games Tournament (TGT) type of cooperative learning model while also analysing the significance of the improvement in learning outcomes of eighth-grade students at SMP Al-Ma’arif Panggung Sampang on the topic of additives. This study uses a quantitative approach with a pre-experimental method designed through a One Group Pretest-Posttest design. The research sample consisted of 22 students selected using the saturated sampling technique. Data collection was carried out through observation, objective tests (pretest and posttest), and the distribution of questionnaires. The results of the descriptive analysis show an increase in the average learning outcomes from 60.00 at the pretest stage to 71.36 at the posttest stage. Furthermore, the results of the parametric statistical test using the Paired Sample t-Test prove a significant difference with a Sig. (2-tailed) value of 0.000 (< 0.05). Based on these findings, it can be concluded that the systematic implementation of the TGT syntax has proven effective in creating an interactive learning atmosphere, reducing boredom, and optimally improving students' cognitive learning outcomes on the topic of additives.